2021
DOI: 10.3390/nano11071641
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Surface Functionalization of Carboxylated Cellulose Nanocrystals

Abstract: In recent years, cellulose nanocrystals (CNCs) have emerged as a leading biomass-based nanomaterial owing to their unique functional properties and sustainable resourcing. Sulfated cellulose nanocrystals (sCNCs), produced by sulfuric acid-assisted hydrolysis of cellulose, is currently the predominant form of this class of nanomaterial; its utilization leads the way in terms of CNC commercialization activities and industrial applications. The functional properties, including high crystallinity, colloidal stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 121 publications
1
22
0
Order By: Relevance
“…This issue is made even more difficult by the intricate functional and anatomical "wiring," the diverse molecular and cellular milieu, and the sophisticated processing of information [ 44 ]. As a reaction to these challenges, an expanding variety of groups are doing research into the characteristics of a wide range of nanoparticles to make use of the benefits that are inherently associated with their nanometer dimensions [ 45 47 ].…”
Section: Nanoneurosciencementioning
confidence: 99%
“…This issue is made even more difficult by the intricate functional and anatomical "wiring," the diverse molecular and cellular milieu, and the sophisticated processing of information [ 44 ]. As a reaction to these challenges, an expanding variety of groups are doing research into the characteristics of a wide range of nanoparticles to make use of the benefits that are inherently associated with their nanometer dimensions [ 45 47 ].…”
Section: Nanoneurosciencementioning
confidence: 99%
“…These two peaks suggested that the esterification of cellulose was successful and that the carboxyl groups are covalently bonded to cotton. Hence, no pretreatments on cotton fabrics were needed for a successful functionalization, which is a significant advantage since most of the feedstocks used for the extraction of carboxylated CNCs require bleach processing prior to hydrolysis 65 . Although our reaction is not regioselective, there is a larger preference for the esterification of cellulose with citric acid at the C6 position 31 .…”
Section: Preparation Of Citrated Cottonmentioning
confidence: 99%
“…The carboxylic groups of CitCNCs can undergo chemical modifications not possible for the sulfate-half ester groups in SCNCs. For example, amidation or esterification with alcohols can be performed on carboxylated CNCs 65 . Additionally, citrate groups serve as reducing agents, capping agents, and chelating agents, and their interactions can be tailored through pH variations.…”
Section: Size and Morphologymentioning
confidence: 99%
“…There are still limited studies on the design of cationic CNC-based antibacterial agents and hence, in this work, we explored the design, synthesis, characterization, and antibacterial properties of wood-based carboxylated CNCs (cCNCs) coated with the cationic polymer, poly(diallyldimethylammonium chloride) (PDDA). cCNCs were prepared via an oxidation method using ammonium persulfate (APS) as a mild, low-cost, and low-toxicity oxidant [ 34 ]. An advantage to the APS process is its versatility in converting different lignocellulosic biomass into cCNCs without the need for pre-treatments of the starting biomass.…”
Section: Introductionmentioning
confidence: 99%